PERANCANGAN SISTEM INFORMASI PENERIMAAN RETRIBUSI PENAMBANGAN BATU ALAM BERBASIS WEB - Muhamad Ikhsan, Cecep; Susandi, Dony (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Regional levies are one of the important sources of Regional Original Income (PAD) because each year contributes significantly to local revenue. However, management of levies in the regions is still not optimal and effective due to a lack of understanding of the importance of better management of retribution funds and security factors in management because it involves regional income. Given the importance and danger of managing a large number of retribution funds, the Information System for receiving natural stone Retribution from Salawangi Village, Bantarujeg District, Majalengka Regency was formed. This system was formed with the intention of facilitating the relevant employee to enter data.